Health and Healthcare in the Habsburg Monarchy Army in the Long 19th Century (Theatrum historiae, 2007)
Healthcare in Austrian Army at the beginning of the 19th century was – like in many other countries – on a very low level; it was lacking experts, auxiliary staff, and its organization was neglected. The experience of relatively frequent wars together with the progress in medicine resulted in numerous changes in Austrian military administration. The changes mainly concerned the increase in the number and qualification of medical staff, application of the up-to-date scientific findings and medical branches (such as bacteriology), improvement of the permanent medical facilities network and preparation of their “field” equivalents at different levels, the provision for medical facilities mobility and their flexibility to the instant needs, improved transport of the ill, their distribution in the out- flines and cooperation with voluntary medical institutions.